Concurrent Participation in Federally-Funded Welfare Programs and Empowerment Toward Economic Self-Sufficiency. Issue 45 (27th May 2019) - Joseph, Rigaud; Potocky, Miriam; Girard, Chris; Stuart, Paul; Thomlison, Barbara
Abstract: This research examined the impact of participation in federal means-tested welfare programs on the attainment and maintenance of economic self-sufficiency. Using the Survey of Income and Program Participation (SIPP), this quasi-experimental investigation compartmentalized 4216 low-income households into an intervention group ( n = 2436) and a comparison group ( n = 1780). Households in the intervention group received one or more welfare benefits for the most part of the 2008–2013 quinquennium. By contrast, those in the comparison group – although eligible for these benefits – did not receive them. The survey respondents were measured repeatedly over a 56-month period to assess whether welfare receipt impacts their household income steadily beyond 150% of the federal poverty level, after controlling for known predictors. Multivariate analyses displayed medium effect sizes indicating that participation in public assistance did decrease the likelihood of economic self-sufficiency. Macro-implications of these findings for poverty and social welfare stakeholders were discussed.